The Scent of Danger: the Impact of Predator Chemical Cues on Emergence from Refuge and Willingness to Autotomize Limbs in the House Cricket (Acheta domesticus) - Pears, J.; Emberts, Z.; Bateman, Bill (Springer, 2018)
Prey can accurately assess predation risk via the detection of chemical cues and take appropriate measures to survive encounters with predators. Research on the chemical ecology of terrestrial invertebrate predator-prey interactions has repeatedly found that direct chemical cues can alter prey organisms’ antipredator behavior. However, much of this research has focused on the chemical mediation of avoidance and immobility by cues from lycosid spiders neglecting other prominent invertebrate predators and behavior such as autotomy. In our study, house crickets (Acheta domesticus) were exposed to cues from cricket-fed orange-footed centipedes (Cormocephalus aurantiipes), red-back spiders (Latrodectus hasselti), an odorous (cologne) control, and a non-odorous control to determine whether direct chemical cues had any influence on two types of anti-predatory behavior: the willingness (latency) to emerge from a refuge and to autotomize limbs. Exposure to C. aurantiipes cues resulted in a significantly slower emergence from a refuge, but exposure to L. hasselti cues did not. Direct chemical cues had no influence on initial autotomy, but exposure to L. hasselti cues did significantly decrease the latency to autotomize a second limb. That cues from L. hasselti had an influence on a second autotomy, but not initial autotomy may be because crickets that undergo autotomy for a second time may perceive themselves to be already at a higher risk of predation as they were already missing a limb. Variation in responses to cues from different predators demonstrates a need to examine the influence of chemical cues from a wider variety of invertebrate predators on anti-predator behavior.